Placing nature : culture and landscape ecology - Nassauer, Joan Iverson (Island Press, 1997)
"Landscape ecology is a widely influential approach to looking at ecological function at the scale of landscapes, and accepting that human beings powerfully affect landscape pattern and function. It goes beyond investigation of pristine environments to consider ecological questions that are raised by patterns of farming, forestry, towns, and cities." "Placing Nature is a groundbreaking volume in the field of landscape ecology, the result of collaborative work among experts in ecology, philosophy, art, literature, geography, landscape architecture, and history. In this book, they consider the goals and strategies needed to bring human-dominated landscapes into intentional relationships with nature, articulating widely varied approaches to the task." "Every possible future landscape is the embodiment of some human choice. Placing Nature provides important insight for those who make such choices - ecologists, ecosystem managers, watershed managers, conservation biologists, land developers, designers, planners - and for all who wish to promote the ecological health of their communities."--Jacket.